2D/2D g-C3N4/TiO2 with exposed (001) facets Z-Scheme composites accelerating separation of interfacial charge and visible photocatalytic degradation of Rhodamine B. (January 2022) - Liu, Xinwei; Chen, Jin; Yang, Lingfu; Yun, Shuhuan; Que, Meidan; Zheng, Huiqi; Zhao, Yang; Yang, Tai; Liu, Zhikang
Abstract: Z-scheme heterojunction was successfully constructed with (001)-TiO2 and g-C3 N4 via electrostatically self-assemble. Z-Scheme heterojunction nanocomposites improve separation efficiency of photogenerated e − -h + pairs, which strengthen visible photocatalytic elimination for Rhodamine B. The g-C3 N4 with narrower bandgap not only forms a stable phase interface with (001)-faceted TiO2 nanosheets, but also provides high productivity of photo-excited charge carries. Meanwhile, the layered graphite carbon in g-C3 N4 owns an excellent ability to transfer electrons. The RhB degradation rate of the g-C3 N4 /(001)-faceted TiO2 hybrid reach up to 99.9% under the visible light for 2 h. This study provided an efficient g-C3 N4 /(001)-faceted TiO2 photocatalyst with Z-Scheme heterojunction structure has emerged as a promising approach to perfect the photocatalytic capacity of photocatalysts. Highlights: Z-scheme heterojunction were constructed in TiO2 /g-C3 N4 via electrostatically self-assemble. Highest active of (001) facets could exist stably in anatase TiO2 by one-step hydrothermal method. Graphite C in g-C3 N4 was considered as electronic transmission channel.